Social Application of Empathy in Serat Wedharaga to Strengthen the Character of Professional Counselor Candidates Based on Cased Method Learning - Henny Indreswari; Khairul Bariyyah; Rizka Apriani; Linka Latifany Falasifa Reidana; Santi Widiasari; Augusto da Costa (Universitas Negeri Semarang, 2025)
Facts in the field show that the empathy skills that prospective counselors have in understanding their counseling, especially in the aspect of empathy have not been comprehensively internalized. This research has three specific objectives (1) to develop a case method learning model guide based on serat wedharaga values to increase the empathy of prospective counselors; (2) the developed model is theoretically tested through the validation of material experts, media, and potential users; (3) The model is empirically tested that the case method learning model is based on the value of serat wedharagas to increase the empathy of prospective counselors. The implementation of this research uses the development method with ADDIE design. The results of the development are in the form of a learning guide that includes sixteen meetings, containing materials, media, and evaluation tools. The developed learning model proved to be theoretically feasible and practically effective, demonstrated through a paired t-test with a value of Sig. (2-tailed) = 0.000, indicating a significant improvement between pretest and posttest. Thus, serat wedharaga value-based learning is effective in increasing the empathy of prospective counselors. Suggestions for the next researcher to conduct follow-up studies related to the development of other learning models to strengthen the professional character of prospective counselors.